PENDAMPINGAN MUSIK INKLUSIF BERBASIS SENI PARTISIPATORIS BAGI ANAK BERKEBUTUHAN KHUSUS DI BAJAWA, FLORES, NUSA TENGGARA TIMUR - Ferdinandus Bate Dopo; Dedy Setyawan; Hermania Bupu; Kanzul Fikri; Sena Radya Iswara Samino; Maria Klarita Sidu; Maria Margaretha Tawa (Universitas Nias Raya, 2026)
The involvement of children with special needs in public music practices remains limited and tends to be confined to special education environments, indicating a gap between musical experiences in schools and social participation in society. This community service project aims to develop inclusive music mentoring practices based on participatory art to foster the participation of 33 students from SLB Negeri Bajawa in outdoor musical activities. The mentoring process ran for eight weeks through stages of initial observation, sound stimulus delivery, response development, group activities, and performance at the Inclusive Music Stage. Evaluation was conducted through observation, field notes, and documentation. Results show that participant involvement developed gradually, marked not by musical technical skills but by increased social interaction, responsiveness to sound stimuli, and the courage to perform in public spaces. Program sustainability is crucial to ensure that the developments achieved can continue consistently.